Perancangan Sistem Informasi Akuntansi Pengeluaran Kas pada Balai Besar Standardisasi dan Pelayanan Jasa Industri Selulosa Bandung dengan Metode Waterfall - Apriliani, Fitria; Aditiarno, Ratnanto; Sufyana, Candra Mecca (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Through this research, it can be seen that the Center for Standardization and Services of the Cellulose Industry uses the SAKTI application in processing cash expenditure data. The SAKTI application itself was made by the Directorate General of Treasury where the application is used by all accounting entities and reporting entities of State Ministries or Institutions including the Center for Standardization and Cellulose Industry Services. This causes problems slowing down access to the SAKTI application due to the large number of entities using the SAKTI application at the same time. Therefore, a companion system planning is made in addition to the main system that is already running with the aim of making it easier for the expenditure treasurer to process cash expenditure transactions when the main system is experiencing problems. The methods used in the study include qualitative methods with descriptive characteristics. The data collection methods used include conducting observations, direct interviews and conducting literature reviews. Research design techniques using waterfall method with Microsoft Visual Studio software. The design of the cash disbursement system created can help the finance department in processing cash expenditure transactions easily, quickly and accurately.